2012
DOI: 10.1039/c1cy00387a
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic enantioselective methodologies using Morita–Baylis–Hillman carbonates and acetates

Abstract: Lately, the use of Morita-Baylis-Hillman carbonates and acetates in organocatalysis has grown exponentially. Since the pioneering work of Kim and coworkers until the last cycloadditions reported by Barbas, a plethora of new methodologies have been developed. The use of these compounds opens a new gate for the synthesis of C-C or C-heteroatom bonds in an enantioselective fashion and under mild conditions giving access to highly functionalized structures. In this review, we aim to cover these exciting reactions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(38 citation statements)
references
References 41 publications
0
38
0
Order By: Relevance
“…The idea was to apply simple acetylation as means of activating the Morita–Baylis–Hillman starting materials (Figure ). Upon reaction with an organocatalyst, such as 4‐dimethylaminopyridine (DMAP), the known intermediate A would be in equilibrium with the starting material ,. Towards introduction of the nucleophile, it was decided to upgrade trichloroacetate precursors to their corresponding trichloromethyl anions through decarboxylation .…”
Section: Introductionmentioning
confidence: 99%
“…The idea was to apply simple acetylation as means of activating the Morita–Baylis–Hillman starting materials (Figure ). Upon reaction with an organocatalyst, such as 4‐dimethylaminopyridine (DMAP), the known intermediate A would be in equilibrium with the starting material ,. Towards introduction of the nucleophile, it was decided to upgrade trichloroacetate precursors to their corresponding trichloromethyl anions through decarboxylation .…”
Section: Introductionmentioning
confidence: 99%
“…Lewis base-catalyzed asymmetric allylic alkylations (AAA) of Morita–Baylis–Hillman (MBH) adducts [56], such as acetates and carbonates, have become an attractive option to access various chiral C - [719], N - [2025], O - [2630], P - [3133] and S -allylic [34] and spirocyclic compounds [3537]. Several protocols have been established to introduce fluorine atoms in AAA of MBH adducts.…”
Section: Introductionmentioning
confidence: 99%
“…After our discovery of this β-ICD-HFIPA method, a number of sophisticated catalytic systems were developed. [1][2][3][4][5][6] This β-ICD-HFIPA method is applicable to chiral α-amino aldehydes 7 that afford the synthetically useful α-methylene-β-hydroxy-γ-amino acid esters 8 11) (Chart 4). It was found that β-ICD-catalyzed reactions of N-Boc-α-amino aldehydes 7 with HFIPA proceeded without racemization to give enantiomerically pure esters 8 and exhibited a marked match-mismatch relationship.…”
Section: Asymmetric Morita-baylis-hillman Reactionmentioning
confidence: 99%
“…Compound 116 was then converted to 118 via 117 in a six-step sequence involving methylation, iodination, and diimide reduction as major transformations. Iodoalkene 118 was then subjected to Stille coupling with stannane 119 111) using Pd(PPh 3 ) 4 , CuI, and CsF in DMF at room temperature to give Z,Z,E-triene 120 in geometrically pure form. When this coupling was carried out using Pd(0) catalyst alone, some extent of isomerization of the triene system was always observed.…”
Section: Synthesis Of Neooxazolomycinmentioning
confidence: 99%
See 1 more Smart Citation